No effect of lipid lowering on platelet activity in patients with coronary artery disease and type 2 diabetes or impaired glucose tolerance - Malmström, Rickard E.; Settergren, Magnus; Böhm, Felix; Pernow, John; Hjemdahl, Paul (Thrombosis and Haemostasis, 2009)
In addition to lowering cholesterol, statins may reduce platelet activity and exert beneficial non-lipid (pleiotropic) effects. We evaluated the effects of two different simvastatin based treatment regimens on platelet reactivity in patients with dysglycemia and coronary artery disease (CAD). Thirty-two patients with type 2 diabetes or impaired glucose tolerance and stable CAD received six weeks of double-blind treatment with simvastatin 80 mg daily (S80; n=16) or ezetimibe 10 mg and simvastatin 10 mg daily (E10/S10; n=16). Total and low-density lipoprotein (LDL) cholesterol, and high sensitivity C-reactive protein (CRP) decreased similarly in the two groups. LDL (mM) decreased from 3.2 ± 0.6 to 1.7 ± 0.7 with E10/S10 and from 3.0 ± 1.0 to 1.4 ± 0.5 with S80 treatment. Platelet function was evaluated by whole blood flow cytometry and turbidimetric aggregometry with agonist stimulation ex vivo before and after treatment. Neither treatment affected basal or adenosine diphosphate (ADP)- or thrombin-induced platelet P-selectin expression, or fibrinogen binding, or platelet-leukocyte aggregation. Similarly, neither treatment affected ADP-induced platelet aggregation. In conclusion, lipid lowering treatment with high dose simvastatin or low dose simvastatin plus ezetimibe did not exert any substantial inhibitory effects on the basal or agonist-stimulated activity of circulating platelets in patients with stable CAD and type 2 diabetes or impaired glucose tolerance.
Keywords: Simvastatin; ezetimibe; ADP; thrombin; platelet activation